Fluorescence, Biological Activity and Spectroscopic Studies of Azo-linked Schiff Base Ligand Type (ONO) and Its Complexes with CrIII, CoII NiII and CdII Ions - Hasan, Hasan A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The precursor [W] [2-(2-(naphthalen-5-yl) diazenyl)-4-amino-3-hydroxynaphthalene-1sulfonic acid] was synthesized from reaction of diazonium salt with 1-amino-2-naphtol-4sulfonic acid. Then the tridentate Schiff base ligand type ONO was synthesized from the reaction of the precursor with salicyaldehyde in 1:1 mole ratio to produce the ligand H2L [2-(2-(naphthalen5-yl) diazenyl)-4-(2-hydroxynaphthalen-3-yl)methyleneamino)-3-hydroxy salicyalene-1-sulfonic acid],the reaction achieved in methanol as a solvent under reflux. Spectroscopic methods IR, U.V, 1H,13C-NMR was used to characterize the ligand. Complexes of [CrIII, CoII, NiII and CdII] ions were also prepared through reaction of ligand with metal salts in 2:1 mole ratio at reflux, using KOH as a base, ethanol as a solvent. Chloride content, molar conductivity and melting point measurements along with I.R and U.V-Vis, atomic absorption (A.A) spectroscopy were used to characterize the complexes.1H-NMR spectroscopy was used to characterize Cd complex. Thermal analysis was used to insure the presence of crystallized H2O molecule in the complexes structure. The following formula was proposed for Cr complex: K[Cr(L)2]. H2O, while CoII, NiII and CdII complexes have the K2[M(L)2].H2O formula. The biological activity of the prepared compounds was studied. Fluorescence properties of the prepared compounds were studied (at room temperature) which indicate that the ligand may behave as strong fluorescent emitter. The complexes also showed fluorescence characteristic with the ligand. The ligand revealed high relative intensity and its fluorescence peak were also shifted to the lower or higher wavelength when compared with the complexes.